Serum anti mullerian hormone and renalase levels in predicting the risk of preeclampsia - Zehra Jamil; Sana Shahid; Erum Baig; Rida Ahmad; Faryal Subhani; Syeda Sadia Fatima (Elsevier, 2019)
Objective: The aim of the study was to explore the association of serum AMH and Renalase with the risk of preeclampsia thereby assessing them as screening tools, reducing the risk of gravid consequences of preeclampsia. Materials and methods: This cross-sectional study recruited n = 95 pregnant women between 14 and 32 gestational weeks. They were categorized as a) women with gestational hypertension (n = 45); b) women with pre-eclampsia (n = 20) and c) normotensive pregnant women (n = 30) according to the ACOG criteria. Anthropometrics data and blood and urine samples were collected. AMH and Renalase levels were measured by ELISA assay. Results: The mean age of study cohort was 27.3 ± 6.2 year and weight was 65.1 ± 14.1 kg. Blood pressures were significantly higher in pre-eclamptic patients versus both the gestational hypertensive females and controls (p < 0.05). AMH was found to be significantly higher in controls but no difference was observed between gestational hypertensive and pre-eclamptic patients. No difference was seen for serum Renalase among the three groups (p > 0.05). AMH showed a negative weak correlation with diastolic blood pressure (r = −0.272; p = 0.008) that remained significant even after adjustment (r = −0.236; p = 0.023) whereas Renalase did not show any difference (r = −0.051; p > 0.05). Females with low levels of AMH were 1.07 times at risk of developing hypertension even after adjustment for age and BMI (p < 0.05). Conclusion: Low AMH levels may lead to hypertension in pregnancy suggesting a role in detecting vascular diseases as well as its effect on ovarian aging. However, further research is required to establish a causal relationship. Keywords: Pre-eclampsia, Hypertension, AMH, Renalase